TCRs with segment TRAV9‐2 or a CDR3 histidine are overrepresented among nickel‐specific CD4+ T cells. Issue 10 (13th May 2020) - Aparicio‐Soto, Marina; Riedel, Franziska; Leddermann, Melanie; Bacher, Petra; Scheffold, Alexander; Kuhl, Heiner; Timmermann, Bernd; Chudakov, Dmitriy M.; Molin, Sonja; Worm, Margitta; Heine, Guido; Thierse, Hermann‐Josef; et al.
Abstract: Background: Nickel is the most frequent cause of T cell–mediated allergic contact dermatitis worldwide. In vitro, CD4+ T cells from all donors respond to nickel but the involved αβ T cell receptor (TCR) repertoire has not been comprehensively analyzed. Methods: We introduce CD154 (CD40L) upregulation as a fast, unbiased, and quantitative method to detect nickel‐specific CD4+ T cells ex vivo in blood of clinically characterized allergic and non allergic donors. Naïve (CCR7+ CD45RA+) and memory (not naïve) CD154+ CD4+ T cells were analyzed by flow cytometry after 5 hours of stimulation with 200 µmol/L NiSO4 ., TCR α‐ and β‐chains of sorted nickel‐specific and control cells were studied by high‐throughput sequencing. Results: Stimulation of PBMCs with NiSO4 induced CD154 expression on 0.1% (mean) of naïve and memory CD4+ T cells. In allergic donors with recent positive patch test, memory frequencies further increased 13‐fold and were associated with markers of in vivo activation. CD154 expression was TCR‐mediated since single clones could be specifically restimulated. Among nickel‐specific CD4+ T cells of allergic and non allergic donors, TCRs expressing the α‐chain segment TRAV9‐2 or a histidine in their α‐ or β‐chain complementarity determining region 3 (CDR3) were highly overrepresented. Conclusions: Induced CD154 expression represents a reliable method to study nickel‐specific CD4+ T cells. TCRs with particular features respond in all donors, while strongly increased blood frequencies indicate nickel allergy for some donors. Our approach may be extended to other contact allergens for the further development of diagnostic and predictive in vitro tests. Abstract : We find increased frequencies of Nickel‐specific memory CD4+ T cells in PBMCs of some nickel allergic individuals, applying a new approach based on CD154 upregulation. High‐throughput sequencing of αβ T cell receptors reveals an overrepresentation of α‐chain segment TRAV9‐2 and CDR3 histidines. Abbreviations: CDR, complementarity determining region; HTS, high throughput sequencing; MHC, major histocompatibility complex; Ni, nickel; NiSO4, nickel sulfate; PBMCs, peripheral blood mononuclear cells; TCR, T cell receptor; TRAV9‐2, TCR α‐chain V‐segment.